Development of a miniaturized 3D organoid culture platform for ultra-high-throughput screening. (17th July 2020) - Du, Yuhong; Li, Xingnan; Niu, Qiankun; Mo, Xiulei; Qui, Min; Ma, Tingxuan; Kuo, Calvin J; Fu, Haian
Abstract: The recent advent of robust methods to grow human tissues as 3D organoids allows us to recapitulate the 3D architecture of tumors in an in vitro setting and offers a new orthogonal approach for drug discovery. However, organoid culturing with extracellular matrix to support 3D architecture has been challenging for high-throughput screening (HTS)-based drug discovery due to technical difficulties. Using genetically engineered human colon organoids as a model system, here we report our effort to miniaturize such 3D organoid culture with extracellular matrix support in high-density plates to enable HTS. We first established organoid culturing in a 384-well plate format and validated its application in a cell viability HTS assay by screening a 2036-compound library. We further miniaturized the 3D organoid culturing in a 1536-well ultra-HTS format and demonstrated its robust performance for large-scale primary compound screening. Our miniaturized organoid culturing method may be adapted to other types of organoids. By leveraging the power of 3D organoid culture in a high-density plate format, we provide a physiologically relevant screening platform to model tumors to accelerate organoid-based research and drug discovery.